2014
DOI: 10.1002/chem.201403061
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blues as a Cathode Material for Lithium Ion Batteries

Abstract: Prussian blues (or iron cyanides) and their analogues are attractive in both fundamental studies and industrial applications owing to their chemical and structural diversity. The large open space in their framework provides tunnels and space for the transport and storage of lithium ions. Two Prussian blues were synthesized by a co-precipitation method. The nanosized Fe4 [Fe(CN)6 ]3 and cubic FeFe(CN)6 deliver reversible capacities of 95 mAh g(-1) and 138 mAh g(-1) , respectively. In comparison, FeFe(CN)6 shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 29 publications
(28 reference statements)
2
76
0
2
Order By: Relevance
“…1(e). The water content of PBN 0.4 C 0.6 is determined to be 10.3%, which is less than that of common PBAs [21]. Thus, this indicates an improved thermal stability of PBN 0.4 C 0.6 .…”
Section: Resultsmentioning
confidence: 95%
“…1(e). The water content of PBN 0.4 C 0.6 is determined to be 10.3%, which is less than that of common PBAs [21]. Thus, this indicates an improved thermal stability of PBN 0.4 C 0.6 .…”
Section: Resultsmentioning
confidence: 95%
“…a–d) Charge–discharge curves of PBAs used as cathode: a) FeFe(CN) 6 in LIBs, reproduced with permission . Copyright 2014, Wiley‐VCH.…”
Section: Applicationsmentioning
confidence: 99%
“…FeFe(CN) 6 was tested as a cathode material for Li‐ion batteries, delivering a charge capacity of 95 mAh g −1 . The charge–discharge curves showed that the main redox peak at 2.8/3.1 V corresponds to reduction/oxidation of low‐spin Fe 2+ /Fe 3+ ions coordinated with the carbon, and a small redox peak at 3.8/3.9 V was assigned to the reduction/oxidation of the high‐spin Fe 2+ /Fe 3+ bonded to nitrogen (Figure a).…”
Section: Applicationsmentioning
confidence: 99%
“…The phase structure and relative crystallinity of the as-prepared samples were first investigated by taking XRD measurements. 23,24 The absorption bands located at 604 and 502 cm À1 can be assigned to the in-plane and out-of-plane deformations of the Fe-C bond, respectively. S1, ESI †).…”
Section: Characterization Of Pb@co 3 O 4 Npsmentioning
confidence: 99%